Negociaciones para la construcción de un régimen internacional de acceso a los recursos genéticos: el camino hacia el protocolo de Nagoya (2014)
The Convention on Biological Diversity (CBD) led the way to the creation of a common international framework to access genetic resources and to share the benefits arising from the utilization of these resources in an equitable and fair way. Despite the Convention text included some regulations on this matter, it was the Conference of the Parties (COP) the one facing a difficult negotiation. It started with the Open-ended Working Group on Access and Benefit-Sharing, and it decisively moved forward in 2010 when Nagoya Protocol was finally adopted during the 10th COP of the CBD. During this legislative process, that actually has just begun, many were the stages the ABS group had to confront to pursue the provisions established in the Cancun Declaration and the CMNUDS. Thus, each COP assumed the responsibility to impel these negotiations, and in each of these meetings multilateral documents were subscribed to consolidate the “International Regime on Access to Genetic Resources”, which is composed by the Nagoya Protocol, Bonn Guidelines, the CBD, and the International Treaty on Plant Genetic Resources for Food and Agriculture.